Efektivitas Pelaksanaan Penyampaian Pelaporan Notaris Berbasis Digital dalam Mendukung Majelis Pengawas Daerah di Provinsi Gorontalo - Harjun Podungge; Andi Inar Sahabat; Gito Alan Ali (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
The background of this research is driven by the inefficiencies of the manual notary supervision and reporting system, which prompted a digitalization innovation through the SENORITA application by the Regional Office of the Ministry of Law and Human Rights of Gorontalo Province. This study aims to analyze the effectiveness of digital-based notary reporting in enhancing the performance of the Regional Supervisory Council (MPD) in Gorontalo Province. The method employed is empirical legal research using a mixed-methods approach (quantitative and qualitative), utilizing primary data collection instruments through interviews and observations, supported by secondary data. The findings indicate that the implementation of the SENORITA application has yielded positive impacts, including reporting time efficiency, improved notary discipline, and facilitated direct monitoring by the MPD. Nevertheless, its implementation still encounters obstacles such as unstable internet network infrastructure, technical glitches within the application, limited digital literacy among users, and the absence of specific regulations governing electronic reporting. The implications of this study underscore the need for comprehensive improvements, encompassing the enhancement of technological infrastructure, the development of system stability, the strengthening of legal frameworks, and continuous socialization, to ensure that the digital transformation in notarial administrative governance operates optimally.